Rethinking disability theory and practice : challenging essentialism - Lesnik-Oberstein, Karín (Palgrave Macmillan, 2020)
Disability Studies has burgeoned as a field of enquiry in recent decades. Yet, as economic pressures on disability provision and benefits continue to increase, questions about disability theory and practice have become more pressing. This inter- and trans-disciplinary volume presents novel approaches to key debates in Disability Studies, particularly about how to think about and define disability. The contributors in Rethinking Disability Theory and Practice address a wide range of issues, including: childhood, gender, sexuality, autism, ADHD, deafness, agency, race, affect, the body and the animal. Diverging from other recent publications in Critical Disability Studies, this volume as a whole aims to challenge essentialism, demonstrating above all the consequences of radically rethinking the roles of language and perspective in constructing identities